(untitled) (Global Journal of Science Frontier Research, 2019)
This paper examines studies to evaluate the economic viability of off-grid photovoltaic PV renewable energy technologies for rural applications in Lafiagi, Kwara State, Nigeria, to meet the government set target. It utilizes the life-cycle cost to estimate a 25 years life-time of an offgrid electrification project and compare with the cost of paying for grid-electrification within the same period. The result shows that such a project is economically viable. The project yield a strong positive pre-tax IRR on equity and a positive pre-tax IRR on assets. A simple payback can only be guaranteed in the project life span. Meanwhile, an equity payback can be completed within 12 years of the project life cycle.